Intraganglionic macrophages: a new population of cells in the enteric ganglia. Issue 4 (18th July 2018) - Dora, David; Arciero, Emily; Hotta, Ryo; Barad, Csilla; Bhave, Sukhada; Kovacs, Tamas; Balic, Adam; Goldstein, Allan M.; Nagy, Nandor
Abstract: The enteric nervous system shares embryological, morphological, neurochemical, and functional features with the central nervous system. In addition to neurons and glia, the CNS includes a third component, microglia, which are functionally and immunophenotypically similar to macrophages, but a similar cell type has not previously been identified in enteric ganglia. In this study we identify a population of macrophages in the enteric ganglia, intermingling with the neurons and glia. These intraganglionic macrophages (IMs) are highly ramified and express the hematopoietic marker CD45, major histocompatibility complex (MHC) class II antigen, and chB6, a marker specific for B cells and microglia in avians. These IMs do not express antigens typically associated with T cells or dendritic cells. The CD45 + /ChB6 + /MHCII + signature supports a hematopoietic origin and this was confirmed using intestinal chimeras in GFP‐transgenic chick embryos. The presence of green fluorescent protein positive (GFP +) /CD45 + cells in the intestinal graft ENS confirms that IMs residing within enteric ganglia have a hematopoietic origin. IMs are also found in the ganglia of CSF1R GFP chicken and CX3CR1 GFP mice. Based on the expression pattern and location of IMs in avians and rodents, we conclude that they represent a novel non‐neural crest‐derived microglia‐like cell population within the enteric ganglia.